2014
DOI: 10.5194/isprsannals-ii-5-267-2014
|View full text |Cite
|
Sign up to set email alerts
|

Survey turned into HBIM: the restoration and the work involved concerning the Basilica di Collemaggio after the earthquake (L'Aquila)

Abstract: ABSTRACT:The HBIM of the Basilica di Collemaggio in L'Aquila is part of the restoration project of the building seriously damaged by the earthquake in 2009. The project "Ripartire da Collemaggio", funded by ENIservizi, involves an interdisciplinary group called to work together toward a common goal: the need of security of the structures and the need of conservation of the architectonic value of the Basilica. Starting from the photogrammetric and laser scanning survey, interpretation and modelling were needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 13 publications
(10 reference statements)
0
97
0
13
Order By: Relevance
“…A lot of developments for as-built BIM are emerging from the adoption of BIM from cultural heritage communities. Many authors have shown the benefits of using BIM for cultural heritage preservation (Fai et al, 2011, Oreni et al, 2014, Wu et al, 2013, Boeykens et al, 2012, Pauwels et al, 2008, Quattrini et al, 2015, Barazzetti et al, 2015. Pauwels et al (2008) describe an approach called Architectural Information Modelling which uses BIM to document geometric data along with appended historical information such as photographs, scanned documents or research material.…”
Section: As-built Bimmentioning
confidence: 99%
“…A lot of developments for as-built BIM are emerging from the adoption of BIM from cultural heritage communities. Many authors have shown the benefits of using BIM for cultural heritage preservation (Fai et al, 2011, Oreni et al, 2014, Wu et al, 2013, Boeykens et al, 2012, Pauwels et al, 2008, Quattrini et al, 2015, Barazzetti et al, 2015. Pauwels et al (2008) describe an approach called Architectural Information Modelling which uses BIM to document geometric data along with appended historical information such as photographs, scanned documents or research material.…”
Section: As-built Bimmentioning
confidence: 99%
“…The first approach has been used in several applications and seems a kind of standard approach to the problem. In the literature there are example for simulating the behaviour of an ancient masonry bridge in Spain (Riveiro et al, 2011), the Trajan's Markets (Brune and Perucchio, 2012), an historic tomb in Turkey (Erkal and Ozhan, 2014) or a church in central Italy after an earthquake (Oreni et al, 2014). In some cases, the reconstructed mathematical model has been refined with the insertion of limited patches of reality-based superficial meshes (Zvietcovich et al, 2014).…”
Section: State Of the Artmentioning
confidence: 99%
“…In addition, heritage BIM library projects such as HBIM provide a set of reusable heritage objects [11][12][13]. BIM has also been used as a basis for the structural analysis of heritage buildings [14].…”
Section: Data Exchangementioning
confidence: 99%